Modelling G3 gas as an alternative gas for SF6 using COMSOL multiphysics - Abelatef Mohammed El-Zein; Ayman Bdrawy Ibrahim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Sulfur hexafluoride (SF6) gas is the most often gas used in high voltage systems as insulating medium and arc quenching because it has many advantages such as high dielectric strength, low boiling point, low toxicity, and stability for a long period. The 1997 Kyoto protocol recommended the elimination of SF6 gas, because its impact on the atmosphere has global warming potential (GWP) equal to 23,500 and an ozone depletion potential (ODP) equal to 0.08. Kyoto protocol recommended alternatives gases for SF6 gas such as CF3CHCL2, and others. In this paper a new gas called a HeptaFluoro-iso-Butyronitrile+CO2 ([(CF3)2CFCN+CO2]) which is known commercially as green global gas (G3) The dielectric strength for the proposed gas is approximately equal to SF6 gas and excellent arc quenching and achieve Kyoto protocol recommendations about using alternative gases with 98% less impact on GWP than SF6 gas also G3 gas maintain the same dimension and overall footprint which is an important economical factor for utilities. The total bond energy analysis of SF6 and G3 gases has been studied. COMSOL multiphysics was used to simulate the SF6 and G3 gases to show the ability of the G3 gas when working in geographic information system (GIS) equipment.